Mocarhagin - Andrews, R.; Berndt, Michael (Elsevier, 2013)
The third edition of the Handbook of Proteolytic Enzymes aims to be a comprehensive reference work for the enzymes that cleave proteins and peptides, and contains over 850 chapters. Each chapter is organized into sections describing the name and history, activity and specificity, structural chemistry, preparation, biological aspects, and distinguishing features for a specific peptidase. The subject of Chapter 243 is Mocarhagin.